Supporting and Expanding Statewide CASA Programs. (14th July 2021) - Brocious, Heidi; Trawver, Kathi R.; Griffin, Rebecca
Abstract: Court Appointed Special Advocate (CASA) programs around the U.S. are searching for ways to increase the number of volunteers they can recruit and retain so more youth in care can be served. Through focus groups and interviews, study authors collected and analyzed qualitative data on the essential tasks of CASA volunteers, while also soliciting ideas regarding program expansion. Four themes were identified: (1) CASA volunteers do what others on the case can't always do; (2) CASA volunteers make an impact on case outcomes; (3) Statewide structures and resources are essential to the program's success; and (4) Program innovations that will improve CASA practice.